2019
DOI: 10.5430/ijfr.v11n1p220
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Efficiency of GCC Banking Sector: An Empirical Comparison of Islamic and Conventional Banks

Abstract: We examine and compare the performance of 63 (21 Islamic and 42 conventional) GCC banks at two tiers, covering the period of 2010–2016. In the first tier, an industry-level analysis is conducted of each country, followed by an individual bank-level analysis in the second tier. Deposits, assets, and capital are taken as inputs to measure the outputs using data envelopment analysis techniques. At the industry level, we find that Islamic banking is at par with-if not better than-conventional banking in all terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…An Islamic financial institution (IFI) is defined as a banking or financial system that is based on the principles of Islam or Sharia Law and is guided by Islamic rules of economics [9][10][11]. These IFIs include banks, welfare institutions, and other lending institutions whose business models are based on Islamic principles [4,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An Islamic financial institution (IFI) is defined as a banking or financial system that is based on the principles of Islam or Sharia Law and is guided by Islamic rules of economics [9][10][11]. These IFIs include banks, welfare institutions, and other lending institutions whose business models are based on Islamic principles [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…An Islamic financial institution (IFI) is defined as a banking or financial system that is based on the principles of Islam or Sharia Law and is guided by Islamic rules of economics [9][10][11]. These IFIs include banks, welfare institutions, and other lending institutions whose business models are based on Islamic principles [4,10]. In the current study, the terms financial institution and financial technologies refer to Islamic banks, technologies, welfare institutions, and lending institutions that provide finances to their customers.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on Internet Banking underscores a paradigm shift in the traditional banking system, showcasing the deep operational and financial changes induced by the adoption of Information and Communication Technology (ICT) tools by both conventional and Islamic banks (Khokhar et al 2020). This shift is observable in the wide range of services and products offered exclusively online, facilitated by several digital tools, leading to increased profits and promising growth opportunities for the banking sector (Abdo 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The banking sector, being at the forefront of digital transformation, admits the paramount importance of leveraging the latest information and communications technologies (Khatoon et al 2020). According to Khokhar et al (2020) the advent of "Fintech" has introduced innovative technologies like blockchain, artificial intelligence, and cloud technologies, which have contributed to enhanced efficiency unparalleled to that produced by traditional processes. This ever-growing evolution of "Fintech" is crucial for both Islamic and conventional finance, calling for its active leverage in this ongoing digital transformation (Khokhar et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There are also some studies, which found the similar findings. For example, Khokhar, I., et al . (2020) found that the Islamic banking performance is better than the conventional banking services.…”
Section: Research Findingsmentioning
confidence: 99%